How to Use SPSS : a step-by-step guide to analysis and interpretation - Cronk, Brian C. (Los Angeles, CA : Pyrczak Pub., 1999)
Addendum for Versons 9.0 and 10.0
Keywords: Social sciences -- Statistical methods -- Computer programs -- Handbooks, manuals, etc